ULTRASOUND-GUIDED ERECTOR SPINAE PLANE BLOCK VERSUS PARAVERTEBRAL BLOCK FOR POST-OPERATIVE ANALGESIA IN POSTEROLATERAL THORACOTOMY (The Research of Medical Science Review, 2025)
Background Posterolateral thoracotomy is a usual method for surgery in the chest and it usually leads to significant post-op pain. Good pain relief is crucial for a smooth recovery and regional blocks are now a main practice in this area. Objectives: to evaluate and compare how much morphine was used by patients after ultrasound-guided erector spinae plane (ESP) block and paravertebral block (PVB), when both blocks were used for posterolateral thoracotomy. Study Design: A Retrospective Observational Study. Place and Duration of Study. The Department of Cardiothoracic Anesthesia Department in RMI Peshawar, from May 8, 2024, to November 8, 2024 Results :60 patients undergoing posterolateral thoracotomy were equally divided into two groups: those with ESP block (Group A) and those with PVB (Group B). For the first two days after surgery, patients were given morphine as prescribed and this use was noted.Group B (PVB) had a daily morphine intake that was significantly less than Group A (ESP): 16.48±9.37 mg versus 33.17±20.34 mg (p=0.000). The trend was the same for people of all ages, genders, BMIs, medical conditions and economic levels. Conclusion: The paravertebral block provides superior postoperative analgesia compared to the erector spinae plane block in patients undergoing posterolateral thoracotomy, significantly reducing opioid requirements.